Long Working Hours and Risk of Nonalcoholic Fatty Liver Disease: Korea National Health and Nutrition Examination Survey VII - Song, Eyun; Kim, Jung A.; Roh, Eun; Yu, Ji Hee; Kim, Nam Hoon; Yoo, Hye Jin; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Baik, Sei Hyun; Choi, Kyung Mook (Frontiers in Endocrinology, 2021)
Background: The global incidence of NAFLD is rising sharply due to various risk factors. As previous studies reported adverse health impact of long working hours on metabolic diseases, such as diabetes mellitus and obesity, it is plausible that NAFLD is also associated with working excessive hours. However, data regarding this issue is limited. Methods: In this cross-sectional study based on Korea National Health and Nutrition Examination Survey VII, 5,661 working adults without previous liver disease or heavy alcohol drinking habits were included. The subjects were categorized into three groups according to working hours: 36–42, 43–52, and 53–83 hours/week. NAFLD was defined using the hepatic steatosis index (HSI), which is a validated prediction model for determining NAFLD. Results: The prevalence of NAFLD (HSI ≥36) increased with longer working hours: 23.0%, 25.6%, and 30.6% in the 36–42, 43–52, and 53–83 hours/week group, respectively (p <0.001). Subjects who worked 53–83 hours/week had higher odds for NAFLD than those who worked the standard 36–42 hours/week (OR 1.23, 95% CI 1.02–1.50, p = 0.033) after adjusting for age, sex, body mass index, smoking, alcohol, exercise, diabetes mellitus, hypertension, serum triglyceride, and total cholesterol. This association was consistent across subgroups according to working schedule (daytime vs. shift workers) or occupation type (office vs. manual workers). In particular, the relationship between long working hours and NAFLD was pronounced in workers aged <60 years and in female workers. Conclusions: Long working hours was significantly associated with NAFLD. Further prospective studies are required to validate this finding with causal relationship.